Implementação de uma prótese ativa para membro superior de baixo custo - Xavier, Ricardo Taoni [UNESP] (2016)
This paper describes the implementation a low cost hand prosthesis, a mechanism constituted by sixteen degrees of freedom, five articulated fingers individually, driven by mechanical tendons. Its structure was made in a 3D printer. For the man-machine interfacing, a shield was developed which performs the acquisition of electromyographic signals, with two channels, SD card storage and an electronic system able to generate a database of movements made by the human hand. The Arduino platform was used for processing and programming. The system contains an app with a programmable drive and insertion movements protocol, providing independence to the user. Tests were conducted in which the implemented system performed movements, after storing various functional hand movements. This was possible due to the development of an algorithm capable of recognizing, quantifying and storing the signals produced by muscle contractions. The implemented active prosthesis worked well for patients with congenital deformity and amputee. The total value of the mechanical and electronic components required to implement the active prosthesis and the use of free hardware and software contribute to the low cost of the device.